Meatsplaining : the animal agriculture industry and the rhetoric of denial - Hannan, Jason, 1976- (Animal publics (Series), 2020)
The animal agriculture industry, like other profit-driven industries, aggressively seeks to shield itself from public scrutiny. To that end, it uses a distinct set of rhetorical strategies to deflect criticism. These tactics are fundamental to modern animal agriculture but have long evaded critical analysis. In this collection, academic and activist contributors investigate the many forms of denialism perpetuated by the animal agriculture industry. What strategies does the industry use to avoid questions about its inhumane treatment of animals and its impact on the environment and public health? What narratives, myths and fantasies does it promote to sustain its image in the public imagination?